Dynamics of pasture contamination with bovine gastrointestinal nematode eggs in the Lerma Valley, Argentina. (FAVE Sección Ciencias Veterinarias, 2022)
The Lerma Valley (LV) is a region located in the central part of the province of Salta, Argentine Republic. The largest dairy production in the province originates in this region. Gastrointestinal nematodiasis is one of the health problems with the greatest economic impact in pastoral-based production systems. The objective of the present work was to characterize the seasonal variation of the elimination of eggs and genera of nematodes to the environment. Fecal matter samples were taken from rearing cattle to count eggs per gram (Epg) and culture for gender determination monthly in three farms in the region. In these, it was possible to observe that the Epg values ​​showed two peaks, which occurred between the beginning of summer and the end of autumn. Regarding the genera/species, the most prevalent were Cooperia pectinata, Haemonchus sp. and Cooperia punctata, followed by Oesophagostomum spp., Trichostrongylus spp. and Ostertagia spp. These results contribute with new evidence to the knowledge of the epidemiology of gastrointestinal nematodes of cattle in the LV region.
Keywords: Gastrointestinal nematodes; cattle; eggs; fecal matter; contamination